Redundancy at Royal Aircraft Establishment, 1946 (1946)
1946 1945-1960 "Redundancy at Royal Aircraft Establishment, 1946" [HFR0144], 1946 The Farnborough Branch of the Association of Scientific Workers reports on the campaign against post war redundancies at the Royal Aircraft Establishment. Over 1000 employees, 40% of the staff, were affected. These were mainly junior scientific officers who had not completed their training and the AScW was concerned at the impact on future availability of scientific manpower. The campaign urged the Government to switch urgent civil aircraft research to Farnborough.